Communication Experience of Indonesian Migrant Workers' Children in the Process of Building Self Concept in Sampang District - Moh. Afdol (Eduvest - Journal of Universal Studies, 2026)
This research aims to explore the communication experiences of children of Indonesian migrant workers (TKI) in Sampang Regency and how these experiences shape their self-concept amid the absence of parental presence. Using a qualitative descriptive approach, the research employed in-depth interviews and light participant observation with five informants aged 13–25 years. The findings reveal that communication between TKI parents and their children occurs infrequently and tends to be practical, focusing on material needs rather than emotional affection. This condition creates ambivalence in self-concept formation, where children feel proud of their parents' economic success yet experience emotional emptiness. Moreover, the social environment strongly influences this process through the "TKI child" label, which brings both social pressure and motivation to develop a positive identity. The study highlights that long-distance family communication serves not only as an exchange of information but also as a crucial space for identity construction and psychological resilience. This research concludes that the communication experiences of migrant worker children shape a distinctive self-concept formation process characterized by ambivalent feelings, defensive self-presentation, and reflective adaptation, where children develop various mechanisms to navigate emotional distance and social labeling. These findings are expected to contribute to the development of family communication and social support programs for children of migrant workers in rural Indonesia.